Structural investigations of the α12 Si–Ge superstructure. (1st February 2015) - Etzelstorfer, Tanja; Ahmadpor Monazam, Mohammad Reza; Cecchi, Stefano; Kriegner, Dominik; Chrastina, Daniel; Gatti, Eleonora; Grilli, Emanuele; Rosemann, Nils; Chatterjee, Sangam; Holý, Vaclav; Pezzoli, Fabio; Isella, Giovanni; et al.
<x xml:space="preserve">Abstract</x> This article reports the X‐ray diffraction‐based structural characterization of the α12 multilayer structure SiGe2Si2Ge2SiGe12 [d'Avezac, Luo, Chanier & Zunger (2012). Phys. Rev. Lett.108, 027401], which is predicted to form a direct bandgap material. In particular, structural parameters of the superlattice such as thickness and composition as well as interface properties, are obtained. Moreover, it is found that Ge subsequently segregates into layers. These findings are used as input parameters for band structure calculations. It is shown that the direct bandgap properties depend very sensitively on deviations from the nominal structure, and only almost perfect structures can actually yield a direct bandgap. Photoluminescence emission possibly stemming from the superlattice structure is observed.